Permeable concrete modified by versatate copolymer

By using vinyl tertiary carbonate copolymers and waste glass powder, copper slag, metakaolin and other alternative cement materials in permeable concrete, combined with sodium hexametaphosphate regulators, the durability and freeze-thaw resistance of permeable concrete in acid rain environments are solved. The problem has achieved high strength, high water permeability and environmental protection effects.

CN116040989BActive Publication Date: 2024-12-27HUBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210854426.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2024-12-27
Estimated Expiration
2042-07-15

AI Technical Summary

Technical Problem

The existing permeable concrete has reduced durability in acid rain environments, is prone to blockage and freeze-thaw damage, and is insufficient in permeability, making it difficult to meet the needs of urbanization construction for high-strength, freeze-thaw resistance and environmental protection.

Method used

Modified permeable concrete by using tert-vinyl carbonate copolymer, by using waste glass powder, copper slag and metakaolin instead of cement as cement, combined with sodium hexametaphosphate as pH regulator, inhibit ettringite expansion and damage and improve pores rate and mechanical properties.

Benefits of technology

It significantly improves the permeability, freeze-thaw resistance and durability of permeable concrete, reduces cement production pollution, enhances corrosion resistance to acid rain and sulfates, and ensures the permeability efficiency and mechanical properties of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003995497290000141
    Figure GDA0003995497290000141
  • Figure GDA0003995497290000151
    Figure GDA0003995497290000151
Patent Text Reader

Abstract

The present application discloses a modified permeable concrete based on tert-butyl ester copolymer. The weight ratio of the modified permeable concrete of tert-butyl ester copolymer is 60-70 parts of copper slag, 20-40 parts of metakaolin, 100-160 parts of basalt and 240-300 parts of waste glass, 1-3 parts of tert-butyl ester copolymer emulsion, 10-20 parts of water, and 1-2 parts of water reducer. Copper slag treated by wet grinding can be used as fine aggregate to improve the flexural and wear resistance of concrete; waste glass powder and metakaolin can be used as cementitious materials to fill smaller cement pores, and evenly dispersed to improve impermeability; waste glass can be used as coarse aggregate to improve the corrosion resistance of permeable concrete to sulfate and acid erosion; tert-butyl ester copolymer emulsion is added to mortar to improve the interface transition zone of permeable concrete to improve the durability of permeable concrete. The materials used in this application are economical and environmentally friendly, the construction process is convenient, and the permeable concrete prepared is highly durable and has a wider range of applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to permeable concrete modified based on versatate copolymer. Background Art

[0002] Ordinary concrete has a dense structure to improve its strength. When there is a lot of rain in summer, the water on the road surface cannot penetrate quickly, resulting in serious urban waterlogging. When the temperature is high, the non-breathable concrete road surface is prone to form a heat island effect, which causes great trouble to the lives of people living in the city. With the rapid development of urbanization and the enhancement of people's environmental awareness, the protection of groundwater resources has also become an important issue. Based on the above problems, permeable concrete, also known as porous concrete, has been developed. It is a skeleton structure composed of aggregates wrapped with paste on the surface. Because it has large pores, it is used to alleviate the urban heat island effect and protect groundwater resources. Nowadays, permeable concrete is widely used in garden squares, pedestrian roads, parking lot pavements, etc. Meeting its use strength and durability is the key to the preparation of permeable concrete.

[0003] The southern part of my country has heavy rainfall. There are large pores in permeable concrete, both through and non-through. The through pores can lead rainwater and other water resources into the ground, which not only alleviates waterlogging but also protects groundwater resources. However, with the development of industrialization, people have been emitting sulfur dioxide and other gases into the air, making rainwater in most parts of my country acid rain. If rainwater stays in non-through pores, it will destroy the strength of permeable concrete, thereby reducing the durability of concrete. In northern my country, winter lasts for a long time and snowfall is heavy. Permeable concrete is easily blocked and the aggregate bonding strength is not high, so it is more damaged by freeze-thaw in ice and snow than ordinary concrete. In addition, after snowing, people usually spread salt on the road to remove ice and snow. If effective protective measures are not taken, deicing salt may cause greater erosion damage to the permeable concrete paste, reducing the durability of permeable concrete.

[0004] Patent CN 113912354 A introduces a method for preparing an enhanced polymer-modified permeable concrete, which is characterized in that dispersible latex powder is used to improve the fluidity of mortar and thickener is used to retain water so that the slurry is wet and sticky and can better wrap aggregates to jointly optimize the structure of cement paste, and then early strength agent CSH crystal nucleus and triethanolamine are added to promote cement hydration, which not only improves the early strength of cement paste but also ensures the stable development of later strength, so that the prepared permeable concrete has good permeability and mechanical properties. However, the coarse aggregate used is basalt and the fine aggregate is river sand. These two materials cannot improve the impermeability of permeable concrete and cannot inhibit the alkali-aggregate reaction of concrete. A large amount of calcium aluminate generated by rapid hydration in the early stage will be damaged by alkali aggregate expansion due to the presence of sulfate in soil or rainwater, and the durability is reduced.

[0005] Patent CN 113683365 A introduces a method for preparing ecological permeable concrete for coastal wetland revetment materials. The method is characterized in that fly ash is used as an auxiliary cementitious material and cement is used as a cementitious material. The hydration of fly ash will produce a large amount of calcium hydroxide to enhance the strength of the material. However, a large amount of calcium hydroxide provides an alkaline environment for alkali-aggregate reaction, which may cause alkali-aggregate expansion damage. Moreover, the large pores of permeable concrete are easily blocked, which may cause sulfate substances to remain in it. External SO42- and internal Ca(OH)2 are the main causes of sulfate erosion of concrete. The recycled concrete aggregate used can reduce the use of natural aggregates, save resources and protect the environment. It can improve the strength and durability of permeable concrete within a certain dosage range. However, the recycled concrete aggregate has poor wear resistance and high porosity compared to natural aggregates, resulting in poor permeability. Moreover, the strength value is measured by testing under steam curing. Whether it can meet the daily use standards remains to be discussed.

[0006] Patent CN 113651575 A introduces a method for preparing a highly durable iron tailings waste rock permeable concrete, which is characterized in that fly ash and silica fume are used to partially replace cement as a cementitious material according to a mass ratio, and the volcanic ash activity of fly ash and silica fume is used to secondary hydrate and consume calcium hydroxide to improve the concrete's impermeability and resistance to sulfate and magnesium salt corrosion. However, fly ash and silica fume of equal mass will generate a large amount of cementitious material, which will reduce porosity and reduce the water permeability coefficient of permeable concrete while increasing strength. The added air entraining agent is used to improve the water retention and cohesiveness of the permeable concrete mixture, so that fine pores exist in the slurry, making the permeable concrete prone to freeze-thaw damage, reducing the scope of application of the permeable concrete. Summary of the invention

[0007] In view of this, the present application provides a permeable concrete modified based on versatate copolymer, which has high impermeability, high strength and high freeze-thaw resistance.

[0008] The present application provides a permeable concrete modified based on versatate copolymer, the raw materials of which include 35-45 parts by weight of A slurry, 35-45 parts by weight of B slurry, 15-25 parts by weight of C slurry, and 1-3 parts by weight of versatate copolymer emulsion;

[0009] The A slurry is a dispersed slurry obtained by wet grinding waste glass powder with water as a medium, the B slurry is a slurry obtained by wet grinding copper slag with water as a medium, and the C slurry is a slurry obtained by wet grinding metakaolin with water as a medium.

[0010] Optionally, the waste glass powder of the A slurry is obtained by crushing waste glass doped with Cr2O3.

[0011] Optionally, 240-300 parts by weight of waste glass added in the form of aggregate is also included.

[0012] Optionally, 100-160 parts by weight of basalt is further included in the form of aggregate.

[0013] Optionally, 5-10 parts by weight of copper slag is further included in the form of aggregate.

[0014] Optionally, the A slurry, B slurry and C slurry each contain a water reducing agent.

[0015] Optionally, the median particle size of the waste glass powder in the A slurry is 3-4 μm, and the rotation speed of the wet grinding is 400-600 r / s.

[0016] Optionally, the copper slag of the B slurry or the copper slag added in the form of aggregate has a silicon dioxide content of about 26%, a particle packing density of 1.9 to 2.15 g / cc, and a fineness modulus of 3.43.

[0017] Optionally, the metakaolin in the C slurry is high-activity metakaolin with a fineness of 1.64-10 μm and a specific surface area of ​​12.56 m 2 / g.

[0018] Optionally, during the preparation of the versatate copolymer emulsion, the emulsifier is obtained by mixing a nonionic flocculant and an anionic flocculant in a mass ratio of 4:1, and the pH regulator is sodium hexametaphosphate.

[0019] The present invention is based on the modified permeable concrete of tert-butyl vinyl carbonate copolymer, which has the following beneficial effects:

[0020] 1. This application uses green glass waste as coarse aggregate. The green color is because the glass contains Cr2O3 chemical raw materials. Glass doped with Cr2O3 as coarse aggregate can inhibit alkali-aggregate reaction and improve the corrosion resistance of permeable concrete to sulfate and acid erosion;

[0021] 2. Using kaolin, waste glass powder and copper slag to completely replace cement as cementitious materials not only reduces the pollution to the environment during cement production and protects the environment, but also consumes a large amount of calcium hydroxide to effectively inhibit the occurrence of alkali-aggregate reaction;

[0022] 3. After wet grinding, the metakaolin has a smaller particle size and higher activity. After being added to cement mortar, it generates more cementitious materials, making the structure denser and effectively improving the freeze-thaw resistance of permeable concrete;

[0023] 4. The strength of permeable concrete mainly depends on the bonding between aggregates. Using copper slag as fine aggregate can effectively improve the mechanical properties of permeable concrete by increasing the paste thickness and the contact area between coarse aggregates to improve the bonding between adjacent aggregates.

[0024] 5. The added tert-butyl vinyl carbonate copolymer can improve the fluidity and viscosity of the slurry, making the slurry more evenly coated on the aggregate surface and increasing the porosity of the permeable concrete.

[0025] 6. With the incorporation of tert-butyl vinyl carbonate copolymer, the air content will increase, resulting in more pores in the permeable concrete and larger pore sizes.

[0026] 7. The addition of tert-butyl vinyl carbonate copolymer will improve the interface transition zone of permeable concrete and form a cross-network connection structure in the coating layer, so that the permeable concrete still has higher mechanical properties while having a large pore size to ensure or even improve the permeability.

[0027] 8. Sodium hexametaphosphate as a pH regulator in tert-butyl vinyl carbonate copolymer can inhibit the continuous growth of ettringite, reduce the occurrence of ettringite expansion damage, and improve the durability of permeable concrete. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0029] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present application, "plurality" means two or more, unless otherwise clearly and specifically defined.

[0030] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0031] The disclosure below provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the various specific processes and material examples provided by the present application, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.

[0032] The invention provides the following technical scheme to prepare permeable concrete modified by tert-butyl vinyl carbonate copolymer, and achieves the following technical effects: waste glass products are used as coarse aggregate to improve the corrosion resistance of permeable concrete to sulfate and acid corrosion, thereby improving the durability of permeable concrete; copper slag is added to permeable concrete as fine aggregate to improve its mechanical properties; metakaolin, waste glass powder and copper slag are used to completely replace cement as a cementitious material, which not only reduces the pollution to the environment during cement production and protects the environment, but also consumes a large amount of calcium hydroxide to effectively inhibit the occurrence of alkali-aggregate reaction, and at the same time, the wet-ground metakaolin has a smaller particle size and higher activity, and the cementitious material generated after being added to cement mortar is more compact, which effectively improves the freeze-thaw resistance of permeable concrete; the added tert-butyl vinyl carbonate can improve the fluidity and viscosity of the slurry, so that the slurry is more evenly coated on the aggregate surface, which not only ensures the porosity but also improves the structural strength, wherein sodium hexametaphosphate as a pH regulator can inhibit the continuous growth of ettringite, reduce the occurrence of ettringite expansion damage, thereby improving the durability of the permeable concrete.

[0033] The copper slag, metakaolin and waste glass used in the present invention all come from industrial waste slag or factory waste; the polycarboxylic acid water reducer used is a polycarboxylic acid water reducer; the materials for preparing versatate vinyl carbonate copolymer can all be purchased online, and because the amount used is small and the aggregates all come from solid waste, the preparation method is economical and environmentally friendly, and is suitable for use in a variety of environments, and has strong applicability value.

[0034] Example 1

[0035] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0036] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0037] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0038] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0039] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0040] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0041] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 160 parts by weight of basalt and 240 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of the versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0042] Example 2

[0043] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0044] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0045] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0046] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0047] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0048] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0049] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 160 parts by weight of basalt and 240 parts by weight of waste glass as coarse aggregate, 10 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0050] Example 3

[0051] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0052] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0053] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0054] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0055] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0056] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0057] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 160 parts by weight of basalt and 240 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 2 parts by weight of versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0058] Example 4

[0059] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0060] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0061] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducing agent, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0062] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0063] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0064] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0065] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 160 parts by weight of basalt and 240 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 3 parts by weight of versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0066] Example 5

[0067] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0068] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0069] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0070] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0071] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0072] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0073] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 140 parts by weight of basalt and 260 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0074] Example 6

[0075] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0076] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0077] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0078] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0079] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0080] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0081] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 120 parts by weight of basalt and 280 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of the versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0082] Example 7

[0083] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0084] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0085] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0086] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0087] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0088] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0089] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 100 parts by weight of basalt and 300 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of the versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0090] Comparative Example 1

[0091] Comparative Example 1 is used to compare with Example 1 to illustrate that when preparing permeable concrete modified by versatate copolymer, when versatate copolymer emulsion is not added, the mechanical properties and porosity of the obtained permeable concrete modified by versatate copolymer are worse.

[0092] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0093] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0094] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0095] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0096] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0097] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0098] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 160 parts by weight of basalt and 240 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly to obtain versatate copolymer modified permeable concrete.

[0099] Comparative Example 2

[0100] Comparative Example 2 is used to compare with Example 2 to illustrate that when copper slag is not added as fine aggregate during the preparation of permeable concrete modified by versatate copolymer, the wear resistance of the obtained permeable concrete modified by versatate copolymer is worse.

[0101] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0102] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0103] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0104] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0105] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0106] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0107] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 160 parts by weight of basalt and 240 parts by weight of waste glass as coarse aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of the versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0108] Comparative Example 3

[0109] Comparative Example 3 is used to compare with Example 6 to illustrate that when preparing permeable concrete modified by versatate copolymer of vinyl carbonate, when cement is used entirely as the cementitious material, the mechanical properties of the obtained permeable concrete modified by versatate copolymer of vinyl carbonate are worse.

[0110] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0111] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0112] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0113] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0114] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0115] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0116] Step 6: Take 100 parts by weight of cement, 15 parts by weight of water, 120 parts by weight of basalt and 280 parts by weight of waste glass as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of the versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0117] Comparative Example 4

[0118] Comparative Example 4 is used to compare with Example 7 to illustrate that when preparing permeable concrete modified by versatate copolymer, when basalt is used entirely as coarse aggregate, the obtained permeable concrete modified by versatate copolymer is more susceptible to alkali aggregate damage.

[0119] A method for preparing permeable concrete modified by versatate copolymer, comprising the following steps:

[0120] Step 1: Put the glass products into a hammer crusher to obtain glass fragments of about 0.25-10 mm, and select the particles with a diameter of 5 mm or more as coarse aggregate through screening, and put the particles with a diameter of less than 5 mm into a drum dry grinder to grind into glass powder;

[0121] Step 2: Take 60 parts by weight of glass powder and 20 parts by weight of water, add 0.1 parts by weight of water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry A;

[0122] Step 3: Take 160 parts by weight of copper slag and 40 parts by weight of water, add 0.1 parts by weight of a water reducer, put them into a planetary ball mill for wet grinding for 20 minutes to obtain slurry B;

[0123] Step 4: Take 160 parts by weight of metakaolin and 25 parts by weight of water, add 0.2 parts by weight of a water reducer, put into a planetary ball mill and wet grind for 40 minutes to obtain slurry C;

[0124] Step 5: Deionized water: emulsifier: pH regulator: potassium persulfate: versatate: butyl acrylate: methyl methacrylate: functional monomer are mixed in a ratio of 10:1:1.1:0.1:5:2.5:0.5 to obtain a versatate copolymer emulsion;

[0125] Step 6: Take 40 parts by weight of slurry A in step 2, 40 parts by weight of slurry B in step 3, 20 parts by weight of slurry C in step 4, 15 parts by weight of water, 400 parts by weight of basalt as coarse aggregate, 5 parts by weight of copper slag as fine aggregate, and 1 part by weight of water reducer, add them into a mixer and stir for 10 minutes to mix evenly, then take 1 part by weight of the versatate copolymer emulsion in step 5, stir evenly for 60 seconds and then discharge the material to obtain versatate copolymer modified permeable concrete.

[0126] The following tests were performed on the permeable concrete specimens prepared in Examples 1 to 7 and Comparative Examples 1 to 4:

[0127] The alkali-aggregate reaction activity adopts the rapid mortar bar method. The specific operation process is to prepare a 25mm×25mm×280mm prism specimen according to the test ratio, put the formed specimen into a standard curing room for curing for 24h±2h, and then place it in a water bath at 80℃±2℃ for 24h±2h. After taking it out, quickly wipe off the surface moisture, and use a length measuring instrument to measure its length, which is recorded as the initial length. Then the specimen is completely immersed in a 1N sodium hydroxide curing solution at a temperature of 80℃±1℃, and cured to an age of 14d±2h. Then the length is measured by the same instrument method, recorded as the final length, and the expansion performance of the specimen is calculated.

[0128] The wear resistance experiment is to cure the specimen under standard curing conditions for 28 days, take it out and dry it in the natural environment for 24 hours, put it in the oven for 4 hours, weigh its mass, put it on the TMS-04 wear resistance testing machine with a head load of 300N, and rotate 70 times at 17r / min to measure its wear depth.

[0129] The freeze-thaw test is carried out according to the single-sided freeze-thaw method in GB / T 50082-2009 "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete"; the sulfate erosion resistance test is carried out according to GB / T 50082-2009 "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete"; the strength measurement is carried out according to GB / T50081-2019 "Standard Test Method for Physical and Mechanical Properties of Concrete"; the permeability coefficient is carried out according to CJJ / T135-2009 "Technical Code for Permeable Cement Concrete Pavement".

[0130] The test results are shown in Table 1 and Table 2:

[0131] Table 1

[0132]

[0133] Table 2

[0134]

[0135] The above cases well show that the added tert-butyl vinyl carbonate polymer can well improve the interface transition zone of permeable concrete, allowing the slurry to be evenly coated on the surface of aggregates, while producing more large-aperture pores, thereby improving the permeability efficiency while ensuring mechanical strength; adding copper slag as fine aggregate can make the aggregate bond more tightly, and a small amount of fine aggregate will not reduce the permeability efficiency of permeable concrete, but can make the structure more compact; using waste glass as coarse aggregate can effectively inhibit the expansion damage of alkali aggregate. Although when the amount of waste glass is increased, it has a certain negative effect on the mechanical properties of permeable concrete, the surface of waste glass is relatively smooth and the porosity of connective tissue is high, which can improve the water penetration efficiency and the corrosion resistance of permeable concrete to sulfate and acid erosion; using kaolin, waste glass powder and copper slag to completely replace cement as cementitious material not only reduces the pollution to the environment during cement production and protects the environment, but also consumes a large amount of calcium hydroxide to effectively inhibit the occurrence of alkali aggregate reaction, further improving the durability of permeable concrete prepared by this method.

[0136] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present application should be covered within the protection scope of the present application.

Claims

1. A permeable concrete modified by versatate copolymer, characterized in that: The raw materials include 35-45 parts by weight of A slurry, 35-45 parts by weight of B slurry, 15-25 parts by weight of C slurry, and 1-3 parts by weight of versatate copolymer emulsion; The A slurry is a dispersed slurry obtained by wet grinding waste glass powder with water as a medium, the B slurry is a slurry obtained by wet grinding copper slag with water as a medium, and the C slurry is a slurry obtained by wet grinding metakaolin with water as a medium; The invention also comprises 240-300 parts by weight of waste glass added in the form of aggregate and 5-10 parts by weight of copper slag added in the form of aggregate.

2. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: The waste glass powder of the A slurry is obtained by crushing waste glass doped with Cr2O3.

3. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: The invention also contains 100-160 parts by weight of basalt added in the form of aggregate.

4. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: The A slurry, B slurry and C slurry each contain a water reducing agent.

5. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: The median particle size of the waste glass powder in the A slurry is 3-4 μm, and the rotation speed of the wet grinding is 400-600 r / s.

6. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: The copper slag of the B slurry and the copper slag added in the form of aggregate have a silicon dioxide content of 26%, a particle bulk density of 1.9-2.15 g / cc, and a fineness modulus of 3.

43.

7. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: The metakaolin in the C slurry is highly active metakaolin with a fineness of 1.64-10 μm and a specific surface area of ​​12.56 m 2 / g.

8. The permeable concrete modified by versatate copolymer according to claim 1, characterized in that: In the preparation process of the versatate copolymer emulsion, the emulsifier is obtained by mixing a nonionic flocculant and an anionic flocculant in a mass ratio of 4:1, and the pH regulator is sodium hexametaphosphate.